The Impact of Social Media Marketing and Brand Image on Purchase Intention and Brand Loyalty in the Case of J&T Express Indonesia - Vincentius Christianto Hartono; Thomas Sadli (iBuss Management, 2022)
Although the global pandemic has detrimentally affected Indonesia, the Indonesian Courier Express and Parcel market has risen due to various aspects. Among all the players, J&T Express is one of the most prominent courier providers being used in Indonesia. Nevertheless, the competitive red ocean market has required J&T Express to upgrade itself to gain market share. Therefore, the researchers would like to analyze how social media marketing and brand image could impact purchase intention and brand loyalty. To conduct the study, respondents with a minimum age of 17 years old, who have ever used J&T Express’ service and seen its official social media content, were selected through simple random sampling method. A total of 104 valid respondents were analyzed using PLS-SEM. The findings show that brand image significantly influenced purchase intention. Additionally, brand loyalty was verified to be significantly influenced by social media marketing, brand image, and purchase intention. However, social media marketing was proven not to significantly influence purchase intention. The researchers believed that it would have been caused by customers who put quality and price as the main selection criteria when choosing a courier service.Keywords: Social media marketing, Brand image, Purchase intention, Brand loyalty, J&T Express Indonesia